3D experimental study on a cylindrical floating breakwater system. (1st October 2016) - Ji, Chun-Yan; GUO, Yu-Chan; Cui, Jie; Yuan, Zhi-Ming; Ma, Xiao-Jian
Abstract: The objective of the present study is to investigate the performance of a cylindrical floating breakwater system based on 3D experimental tests. The experiments were carried out in the wave basin (36 m* 60 m* 1.5 m )of the Ocean University of China. The cylindrical floating breakwater system consists of 10cylindrical floating breakwater units and 10mesh cages with balls in them, connected by 18 connectors and moored by a taut mooring system. The wave transmission coefficients, reflection coefficients, dissipation coefficients and motion responses of the floating breakwater are measured in both oblique and beam sea conditions. It is found that with the increase of the wavelength, both of the wave transmission coefficients and motion response amplitude of the FB system suffers an increase before it reaches its peak value, followed by a decrease trend. It can be concluded from the experiments that the proposed FB system has a satisfactory performance and it can be used to a wide range of sea conditions. Highlights: A new type of cylindrical floating breakwater (FB) system was proposed. 3D experimental tests were conducted to investigate the performance of the new FB system. Wave transmission and reflection coefficients were measured. Motion responses of FB are measured in both oblique and beam sea conditions.